2008
DOI: 10.1021/ic702002m
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of A Caged Zn2+ Probe, 8-Benzenesulfonyloxy-5-N,N-dimethylaminosulfonylquinolin-2-ylmethyl-pendant 1,4,7,10-Tetraazacyclododecane, and Its Hydrolytic Uncaging upon Complexation with Zn2+

Abstract: 8-Benzenesulfonyloxy-5- N,N-dimethylaminosulfonylquinolin-2-ylmethyl-pendant cyclen (BS-caged-L(4), BS = benzenesulfonyl) was designed and synthesized as a "caged" derivative of a previously described Zn(2+) fluorophore, 8-hydroxy-5- N,N-dimethylaminosulfonylquinolin-2-ylmethyl-pendant cyclen (L(4)) (cyclen = 1,4,7,10-tetraazacyclododecane). In the absence of metal ions and in the dark, BS-caged-L(4) (10 microM) showed negligible fluorescence emission at pH 7.4 (10 mM HEPES with I = 0.1 (NaNO3)) and 25 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 117 publications
4
32
0
1
Order By: Relevance
“…1 shows the emission spectrum of 1 (5 mM) in the absence of Zn 2ϩ in 10 mM N-(2-hydroxyethyl)piperazine-NЈ-2-ethanesulfonic acid (HEPES) (pH 7.4) with Iϭ0.1 (NaNO 3 ) at 25°C (excitation at 338 nm) (the emission spectra was obtained by rapid scanning (500-1000 nm/min)) and curve (b) shows a spectrum obtained after Zn 2ϩ -promoted hydrolysis of 3 (via its Zn 2ϩ complex 4) for 3 h in the dark, as previously reported. 39) On the other hand, the photoirradiation of a mixture of 3 (5 mM) and Zn 2ϩ (5 mM) at 328 nm, gave curve (c) having an emission maximum at 510 nm, which is in good agreement with curve (d) for 2 (5 mM) (emission maximum at 512 nm). Based on the observation in 1 H-NMR (Figs.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…1 shows the emission spectrum of 1 (5 mM) in the absence of Zn 2ϩ in 10 mM N-(2-hydroxyethyl)piperazine-NЈ-2-ethanesulfonic acid (HEPES) (pH 7.4) with Iϭ0.1 (NaNO 3 ) at 25°C (excitation at 338 nm) (the emission spectra was obtained by rapid scanning (500-1000 nm/min)) and curve (b) shows a spectrum obtained after Zn 2ϩ -promoted hydrolysis of 3 (via its Zn 2ϩ complex 4) for 3 h in the dark, as previously reported. 39) On the other hand, the photoirradiation of a mixture of 3 (5 mM) and Zn 2ϩ (5 mM) at 328 nm, gave curve (c) having an emission maximum at 510 nm, which is in good agreement with curve (d) for 2 (5 mM) (emission maximum at 512 nm). Based on the observation in 1 H-NMR (Figs.…”
Section: Resultssupporting
confidence: 64%
“…We were able to confirm that the benzenesulfonyl ester of 3 is removed by a nucleophilic attack of Zn ) to give 2. 39,40) During a study of the hydrolytic uncaging reaction of 4, we found that 3 undergoes photolysis to yield 1, whose emission increased upon the addition of Zn . In this study, we report on the photolysis of 3, 4, 8-quinolinyl sulfonate derivatives that contain no metal chelating group (5)(6)(7)(8), and related compounds in aqueous solution (Chart 2).…”
mentioning
confidence: 99%
“…15,24,25) We previously reported that substituted 8-quinolinyl sulfonates such as 1a, e and f undergo photochemical S-O bond cleavage reactions to afford the corresponding 8-quinolinols (2a, e, f) and sulfonate (3) by photoirradiation of aqueous solutions at ca. 300 nm (Chart 1), [26][27][28] which was found during a study of Zn 2ϩ -selective fluorescent probes having 8-quinolinol side chains. [26][27][28][29] A comparison of the photoreactivity of various 8-quinolinyl sulfonate (8-QS) derivatives suggested that the photoreaction efficiency is dependent on the nature of the substituent groups attached to the 8-quinolinol moiety rather than those on the sulfonate unit.…”
mentioning
confidence: 70%
“…[1,2] It plays diverse roles in multiple biological processes. [3][4][5][6][7][8] A disorder of the Zn 2+ metabolism is closely associated with many severe neurological diseases. [9,10] Unlike other biological transition metal ions, Zn 2+ does not give any spectroscopic or magnetic signals due to its 3d 10 4s 0 electronic configuration.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Unlike other biological transition metal ions, Zn 2+ does not give any spectroscopic or magnetic signals due to its 3d 10 4s 0 electronic configuration. [1,3,11] Fluorescence stands out as a suitable method for real-time and real-space imaging of Zn 2+ without cell damage. Although many fluorescent indicators for Zn 2+ have been designed and synthesized, none can perfectly satisfy all the requirements (see refs.…”
Section: Introductionmentioning
confidence: 99%